SENTENCE STRUCTURE AND RHETORICAL STRATEGIES OF HEADLINES IN NEWS REPORTS - Xayrullayeva Xonzoda Tolibjon qizi (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This article examines the headline studies in The New York Times and Xalq so’zi, applying Mann and Thompson’s nucleus-satellite model along with Simpson’s stylistic approach. It sheds light on how rhetorical decisions affect the meanings, emphasis and perception of an audience. The analysis indicates that The New York Times employs a blend of simple, complex, and compound sentence constructions within their headlines. Such choices augment clarity, contrast, emphasis, and emotional appeal through evocative language and evaluative adjectives. In comparison to The New York Times, Xalq so’zi headlines predominantly utilize simple declarative sentences with neutral phrases. The key focal point is placed at the tail end of the sentence, surrounded by a bland tone and a lack of stylistic flourishes. The study demonsrates a tendency within English-language news to prioritize impact and immediacy, while experiencing under formal structure and context in Uzbek news. This highlighting of contrast reveals the broader cultural and journalistic norms that define distinct rhetorical strategies across language and national media boundaries. The article contributes to comprehend how language shapes the public discourse and interpretation of the news.